Evaluasi Sistem Pembebanan Sistem Kelistrikan Gedung Fakultas Ekonomi Universitas Lancang Kuning - Abrar - Tanjung (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Electrical energy lines are the main needs in everyday life and for industrial needs. Because electrical energy channels are easy to send and convert into other forms of energy. The supply of stable and continuous electrical energy is an absolute requirement that must be met in meeting the needs of electric power. The Faculty of Economics building consists of two two-story buildings that are used for academic, administrative and lecture activities. The use of the room is equipped with electrical equipment, such as installation of air conditioners, lighting, computers, infocus and other additional equipment. As a result of the installation of electrical equipment, it caused disturbances and problems in the electrical system in the Economics Faculty Building. This research was conducted to evaluate the Building Load for the Faculty of Economics, University of Lancang Kuning. Based on the results of the discussion, an evaluation was obtained at the Unilak Faculty of Economics building, the average current at 3 phase 380 volts was 51.3 amps, the power capacity was 197 kW, the voltage drop was 24.1 volts, the power loss was 908.8, 89 watts (0.909 kW) and the value of grounding resistance is 22.15 ohms.